Flood management in urban Senegal: an actor-oriented perspective on national and transnational adaptation interventions. (3rd April 2018) - Schaer, Caroline; Thiam, Mame Demba; Nygaard, Ivan
Abstract : In Senegal, considerable development assistance has been allocated to addressing the problem of repeated flooding in urban areas, involving changing thematic objectives, from short-term disaster relief to wide-ranging sanitation and drainage programmes. In spite of these numerous flood management interventions, the number of flood victims in Senegal's urban centres has increased steadily since 1999. This article contributes empirically and conceptually to recent studies highlighting poor national disaster risk management frameworks in West Africa, by investigating how floods have been managed in Senegal and why this management has not led to the results expected by the population. The article finds that the configuration of flood management policies and programmes in urban Senegal points towards three key intertwined issues which have influenced the limited achievements of flood management in urban areas. These include, but are not restricted to, the political and personal appropriation of flood management-related processes, the reinforcement of the dichotomy between central government and municipalities, and a fragmented institutional framework with overlapping institutions.